A Critical Investigation on Weld Bead Defect Detection System Using IoT - Kolisetty Aditya V E, Anish P, Samuel William S, Balaji Ramachandran (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Welding is a process of joining two metals under the application of heat. During the welding process, there is a chance for the occurrence of an undesired irregularity in the form of a defect. Detection of defects formed during Welding is crucial. Under service conditions, these defects lead to the failure of structures and loss of property. Nowadays there is tremendous growth in the field of Internet-of-things. It has many advantages and created a great effect in the manufacturing Industry. By using the Internet-of-Things (IoT) the inspection is done without human intervention and can monitor the defects of weld using the sensors, analyzing and uploading the data into the cloud and visualizing it in the web on any device, anytime, anywhere. The implementation of IoT in welding for weld bead defect defection decreased the inspection time thereby increased production. By analyzing the data through the Internet-of-things the process is automated and can identify the defects using different sensors for measuring the various performance parameters that govern the weld bead quality. This paper describes the various sensing methods based on infrared, radiography, vision, Ultrasonic, acoustic, spectrography techniques and analyzing the data obtained from the sensors, and visualizing the data onto the Thing Speak website by sending it to Cloud using the Internet-of-Things. The weld bead defect detection using IoT can be implemented in the Manufacturing Industry for real-time weld defect monitoring during the welding process.